Model Simulasi untuk Menentukan Harga Pokok Pembelian Tandan Buah Segar di Pabrik Kelapa Sawit Berdasarkan Analisis Data Historis Harga - Budianto, Yusuf; Mubarok, Faizul (Magister Ilmu Akuntansi Universitas Jambi, 2026)
This study aims to develop a simulation model for determining the Cost of Fresh Fruit Bunches (FFB) Purchase Price at palm oil mills, based on historical data and key production factors, including CPO price, PK price, production yield (OER and KER), processing wages, and transportation costs. The research employs an econometric approach using the Vector Error Correction Model (VECM) to examine both short-term and long-term relationships among the variables. The findings indicate that CPO and PK prices have a significant positive effect on FFB purchase price, while production yield contributes positively and significantly in the long run. Conversely, processing wages and transportation costs show a negative effect on FFB cost. The negative and significant Error Correction Term (ECT) demonstrates the presence of a price adjustment mechanism that drives the FFB price toward long-term equilibrium. In conclusion, the developed model effectively captures the dynamic interactions between market and production factors, supporting strategic pricing and enhancing profitability in the palm oil industry.